TRANSFORMATION OF BUSINESS MODELS OF ENTERPRISES IN THE CONDITIONS OF WAR - FERTIKOVA, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the study is to determine the impact of changes in the micro and macro environment on business during a full-scale war and directions for modifying business models that ensure the survival and development of business structures. The methodological basis of the research is А. Osterwalder's and I. Pigneur’s approach to business modeling. In the study it was determined that the war caused the emergence of new consumer segments. There are displaced persons, the state or volunteers, consumers with specific needs due to the special circumstances created by the war. As a result of changes in the demographic, socio-economic characteristics of society, business must rethink the characteristics of existing market segments. The value proposition can be modified taking into account the growth of national self-awareness, an increase in psychological stress, and changes in consumer priorities in wartime conditions. Problems with the organization of physical movement of goods increase the relevance of e-commerce. There is a need to review the channels and quality of communications to attract consumers to form long-term relationships with them, because consumers are more particular about the content and timeliness of messages from sellers during a war. Review of key segments, value proposition prompts to make changes to the range of goods and services that ensure incomes, sales organization, payment methods. An increase in the cost of resources, primarily raw materials, direct loss of property, a decrease of availability of financial resources, and the loss of human capital during the war causes the need to review the priority of resources for the company, and the search for new ways of attracting them. Determination of key types of activities is carried out under the influence of adjustment of consumer segments and available resources. Since many businesses lose the ability to fulfill previously obligations, companies need to look for new key partners, and the increase in the price of resources and the drop in client incomes increases the urgency of cost optimization.
Keywords: business model; war; consumer segments; value proposition; incomes; costs